ORGANOLOGI ALAT MUSIK HANDPAN BUATAN DANIV VERYANA DITINJAU DARI PROSES PEMBUATAN - Dimas, Dimas Aryo Maulana Agsha Sahkanto; Supriadi, Didin; Saryanto (Program Studi Pendidikan Musik, 2020)
This research aims to describe the organology of handpan musical instruments made by Daniv Veryana in terms of the manufacturing process. This research focuses on Organology as seen from its physical classification, namely, the first criteria of raw materials / basic materials. Second, the shape and size. Third instrument, parts. Fourth, the manufacturing process. Fifth, the tuning or tuning process. This research uses qualitative methods and descriptive type. Researchers in this case made observations through a video of the manufacturing process sent directly by the resource person Daniv Veryana, in order to open the Handpan manufacturing process, as well as through literature studies and utilization studies in order to obtain optimal data by making a complete application and eliminating the findings. The results obtained are showing the process of making an accepted handpan musical instrument: Steel plate is intact, according to size, ring clamp, making the main dome, forming molds for dimpel / mortar and molding ding, hardening steel, tuning or tuning process. then the tools used in the process of making handpanit: hammer, large, hammer, medium, hammer, small all wrapped in plastic and rubber, drums, rings, ding molds, dimpel / dimple molds, ear muffs, steel scissors, tongs, stoves roses, 3kg gas, and canned welding gas. The material consists of steel containing 1mm and steel glue.